2009
DOI: 10.1001/jama.2009.1267
|View full text |Cite
|
Sign up to set email alerts
|

Immediate vs Delayed Intervention for Acute Coronary Syndromes

Abstract: HE OPTIMAL INTERVENTION IN the treatment strategy of patients presenting with acute coronary syndromes without ST-segment elevation (NSTE-ACS) has been debated for years. Numerous studies, randomized trials, and metaanalyses have investigated the potential benefits of invasive over conservative strategies, and most have suggested a prolonged advantage of an invasive approach for the prevention of death or myocardial infarction (MI), particularly among high-risk patients. 1-14 If an invasive strategy is general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
3
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(150 citation statements)
references
References 33 publications
6
137
3
4
Order By: Relevance
“…This result is supported by recent reports that early intervention made no difference in preventing primary outcome as compared with delayed approach. [20][21][22] Although our study was not differentiated in accordance with risk stratification in NSTEMI, it suggests that not only appropriate intervention time but also the presence of complete final coronary flow through any device procedure or medial approach might affect less than expected in NSTEMI patients.…”
Section: Discussionmentioning
confidence: 62%
“…This result is supported by recent reports that early intervention made no difference in preventing primary outcome as compared with delayed approach. [20][21][22] Although our study was not differentiated in accordance with risk stratification in NSTEMI, it suggests that not only appropriate intervention time but also the presence of complete final coronary flow through any device procedure or medial approach might affect less than expected in NSTEMI patients.…”
Section: Discussionmentioning
confidence: 62%
“…The amount of time between a patient's arrival at the ES and the time the blocked artery is opened, the so called "doorto-balloon time" in primary angioplasty or "door-to-needle time" in fibrinolysis, can be compromised during off-hours, and fibrinolytics are preferred to primary angioplasty for STEMI. Although it has not been established that the early invasive strategy results in lower mortality in NSTEMI, some clinically or hemodynamically unstable patients can benefit from that procedure 8,10 . The baseline clinical characteristics of the patients studied were similar, except for the higher prevalence of UA for arrival during regular hours, and of NSTEMI for arrival during off-hours.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes with Early Implementation of the ACC/AHA Guidelines (CRUSADE) registry, 11 very early intervention was associated with a trend toward a survival benefit. Finally, in a recent multicenter trial, 12 an early (≤24 hours) invasive strategy in NSTEMI patients showed advantage over a delayed invasive 13 only 8% of the patients in the early group has been treated with GP IIb/IIIa inhibitors, and in the ABOARD trial, 14 most of the patients in the deferred intervention were treated very early (≤24 hours from admission). The benefit of a fast invasive treatment may be linked to the high prevalence of basal impaired myocardial perfusion in NSTEMI patients, even with upstream use of GP IIb/IIIa inhibitors.…”
Section: Discussionmentioning
confidence: 98%